Factors Related to Malnutrition in Children Under Five Years with Congenital Heart Disease - Amani Sakinah Augiani; Sri Endah Rahayuningsih; Dewi Marhaeni Diah Herawati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Congenital heart disease (CHD) is the most frequent type of heart disease that occurs in children. Children with CHD are more vulnerable to suffer impaired nutritional status related to morbidity and mortality. The nutritional status, however, may not be influenced only by CHD, but also by other factors.. The study was conducted to identify factors related to malnutrition in children with CHDMethods: This cross-sectional study involved 86 children with CHD recruited from Dr. Hasan Sadikin General Hospital Bandung from October to November 2015. Data collected in this study were obtained by conducting anthropometric measurements, interviewed the parents (obstetric history, patient’s medical history and socioeonomic status) and from medical records (the type and time of CHD diagnosis, other diseases that accompanied the CHD). The collected data were presented by frequency distribution. Results: There were 46.5% patients who had nutritional disturbance. Malnutrition in males and patients with Tetralogy of Fallot were higher than other groups. Almost half patients with maternal history of passive smoking during pregnancy had nutritional disturbance. The most common disease found was diarrhea followed by lower respiratory infection. Percentage of normal children in low-income parents group was lower than the high-income group. Conclusions: Nearly half of patients have nutritional disturbance. Percentage of nutritional disturbance in male was higher compared to female. Active and passive smokers, Tetralogi Fallot, diarrhea, lower respiratory infection and lower income were factors contributed to malnutrition. [AMJ.2017;4(1):111–7]DOI: 10.15850/amj.v4n1.1031